2018
DOI: 10.3389/fimmu.2018.01387
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 Stimulates the Expansion of Regulatory Hematopoietic Stem and Progenitor Cells in Type 1 Diabetes

Abstract: Hematopoietic stem and progenitor cells (HSPCs) are multipotent stem cells that have been harnessed as a curative therapy for patients with hematological malignancies. Notably, the discovery that HSPCs are endowed with immunoregulatory properties suggests that HSPC-based therapeutic approaches may be used to treat autoimmune diseases. Indeed, infusion with HSPCs has shown promising results in the treatment of type 1 diabetes (T1D) and remains the only “experimental therapy” that has achieved a satisfactory rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…PGE2 regulates hematopoietic stem/progenitor cell (HSC/HSPC) homeostasis 147 , 148 and modulates hematopoietic potential 149 . It's known that PGE2 enhances HSC homing, engraftment, survival, and expansion 148 , 150 , 151 . Researchers also reported that EP4 is a key receptor involving PGE2-mediated positive regulation of HSC/HSPC 152 , 153 .…”
Section: The Role Of Pge2 On Organ Repair and Regenerationmentioning
confidence: 99%
“…PGE2 regulates hematopoietic stem/progenitor cell (HSC/HSPC) homeostasis 147 , 148 and modulates hematopoietic potential 149 . It's known that PGE2 enhances HSC homing, engraftment, survival, and expansion 148 , 150 , 151 . Researchers also reported that EP4 is a key receptor involving PGE2-mediated positive regulation of HSC/HSPC 152 , 153 .…”
Section: The Role Of Pge2 On Organ Repair and Regenerationmentioning
confidence: 99%
“…Apart from CXCR4 [26], it is the modulation of PD-L1 expression, which represents an attractive target for enhancing immunoregulation by HSPCs [24,25]. Interestingly, PGE2-analogs increase the expression of CXCR4 and PD-L1 [27]. Hence, it is attractive to explore, if treprostinil can be repurposed to facilitate AHSCT.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to patients with T1D, the use of AHSCT obtained significant insulin independence and a well-preserved glycometabolic control in the short and mid-term follow-up (Figure 1A and Table 1) (17,31,34,35). Also, an increase in Cpeptide levels and C-peptide area under the curve (AUC) measurement were detectable in AHSCT-treated T1D patients as compared to baseline, and only minor adverse events were registered in the mid-term (25,36). A reduction of the T-helper-1 and T-helper-17 subsets was also observed in the short-term (37).…”
Section: Hscs In Type 1 Diabetes: the Human Landscapementioning
confidence: 92%
“…The use of ADAM3100, which antagonizes the CXCL12 receptor SDF-1, was associated with increased mobilization of HSCs and T cells, and delayed onset of experimental autoimmune diabetes in NOD mice (24). Recently, a defect in PDL-1 expression has been demonstrated in HSCs of NOD mice, which was associated with a reduced immunomodulatory function (9,25). Genetic and pharmacological modulation of PDL-1 on HSCs restored the HSCs immunomodulatory properties, reset the immune balance and prevented the onset of T1D.…”
Section: Hscs In Type 1 Diabetes: the Murine Scenariomentioning
confidence: 99%